PENGARUH MANAJEMEN TALENTA DAN WORK-LIFE BALANCE TERHADAP RETENSI KARYAWAN GENERASI Z DI SEKTOR JASA KOTA SERANG: PERAN MEDIASI KEPUASAN KERJA - Cokorda Agung Wibowo; Andriyansah Setiawan (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2026)
The paradox of high unemployment alongside high turnover rates among Generation Z in the service sector requires a targeted human resource strategy. This study investigates the effect of Talent Management and Work-Life Balance (WLB) on Generation Z Employee Retention, with Job Satisfaction acting as a mediating variable. Conducted in the service sector of Serang City, the research employs a quantitative causal-associative design. Data were collected via purposive sampling from 100 Gen Z employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The empirical results demonstrate that Talent Management and WLB significantly and positively impact Job Satisfaction. Furthermore, Talent Management and Job Satisfaction directly influence Employee Retention. However, a critical finding reveals that WLB does not directly affect Employee Retention; it requires Job Satisfaction as a full mediator. Talent management also partially mediates retention through job satisfaction. The study concludes that WLB acts as a hygiene factor, whereas talent development and job satisfaction are the primary drivers of retention. Managerial implications suggest shifting from generic retention strategies to personalized talent development and meaningful work-life integration.